2021
DOI: 10.21608/ejchem.2021.78774.3853
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silver Nanoparticles, Medium Composition and Growth Regulators on in vitro propagation of Picual Olive Cultivar

Abstract: Micro-propagation of olive provides the possibility of mass production true to type plants with appropriate attributes in short period of time, compared to conventional methods. Micropropagation of olive requires optimization of protocols adapted to specific cultivars requirements. This experiment was carried out during 2020 and 2021 seasons in tissue culture laboratory of Pomology Department, Faculty of Agriculture, Cairo University in order to evaluate the potential effects of Nano silver at 0, 5, 10 and 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…; while the higher concentration (20 and 30mg l − 1 ) recorded a lower leaf number per shoot of Dolce cv. Our results confirm that AgNPs can lead to an improvement in plant growth, which is consistent with our previously published data [ 42 , 43 ]. The obtained results indicated that AgNPs had a stimulatory effect on shoot regeneration of in vitro growing olive shoots of both cultivars and the impact of nanoparticles on shoot growth was highly dependent on NP concentrations [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 93%
“…; while the higher concentration (20 and 30mg l − 1 ) recorded a lower leaf number per shoot of Dolce cv. Our results confirm that AgNPs can lead to an improvement in plant growth, which is consistent with our previously published data [ 42 , 43 ]. The obtained results indicated that AgNPs had a stimulatory effect on shoot regeneration of in vitro growing olive shoots of both cultivars and the impact of nanoparticles on shoot growth was highly dependent on NP concentrations [ 44 , 45 ].…”
Section: Resultssupporting
confidence: 93%
“…[103] and O. europaea cv. Picual [104]. Three NPs, i.e., AgNPs, selenium (SeNPs), and chitosan (CSNPs), were utilized in different cultivars of O. europaea (Manzanillo, Picual, and Koroneiki), and AgNPs showed positive effect on shoot growth, whereas CSNPs and control media had less effectiveness and SeNPs exerted a negative effect [36].…”
Section: Metal Npsmentioning
confidence: 99%
“…Many studies stressed the positive effect of nanomaterials foliar application [30]. Attractive strategies to deal with the PVY problem include the development of new antiviral nanoparticles and using tissue culture techniques to facilitate the propagation of virus-free materials to limit viral transmission [31]. Both approaches of antiviral nanoparticles and tissue culture technique are essential and eventually a combination of the two techniques will be the most effective strategy in controlling the PVY epidemic by diminishing the incidence of plant-to-plant transmission events [32].…”
Section: Introductionmentioning
confidence: 99%